Deterioration and conservation of 19th century malay peninsula manuscripts - Sharifah Tahirah binti Syed Kamarulzaman (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2014)
Many scholars have mainly emphasized on the characteristics and the background history of Malay manuscripts. However, there is lack of study on the problems faced by Malay manuscripts. The aim of this study is to have a better understanding about the deterioration factors that are commonly faced by Malay manuscripts of the 19th century from the Malay Peninsula and to establish recommendations for the conservation and restoration of the manuscripts. The main objective of this study was to identify the properties and physical appearances of the selected Malay manuscripts and their deterioration factors. This study was carried out also to identify preventive measures and techniques for conserving and restoring old Malay manuscripts. This study was conducted in the Islamic Arts Museum Malaysia and the National Library Malaysia. Thirty-five samples of Malay manuscripts were selected; 25 from the Islamic Arts Museum Malaysia and 10 from the National Library Malaysia. Two out of the 35 manuscripts were selected as case studies for detailed observations. The conditions of each of the 35 samples were investigated by using visual analysis technique with the help of non-destructive instruments such as magnifying glass, microscope, pH paper strips and photographic documentation. A condition checklist was designed to investigate and evaluate the deterioration of the selected Malay manuscripts. In this process, the physical condition of the manuscripts that were affected by environmental, biological, chemical and mechanical factors were examined. The results reveal that 39 % of the Malay manuscripts were affected by environmental factors and 60% of the selected Malay manuscripts were in bad conditions where the manuscripts had experienced major deterioration. The findings show that 34 types of deteriorations were identified, which include dust and dirt depositions, insect infestation, the presence of fungus, water stains, brittleness, folds, creases, abrasion and others. The highest occurrences of deterioration were dirt and dust depositions, which was on 100% of the selected manuscripts. In conclusion, this study has established the problems faced by Malay manuscripts and offers suggestions on restoration of 19th century Malay Peninsula manuscripts. The author recommends further research to be established for improving the conditions and extending the lifespans of 19th century Malay Peninsula manuscripts.